The meaning in grandiose delusions: measure development and cohort studies in clinical psychosis and non-clinical general population groups in the UK and Ireland. (October 2022) - Isham, Louise; Sheng Loe, Bao; Hicks, Alice; Wilson, Natalie; Bird, Jessica C; Bentall, Richard P; Freeman, Daniel
Summary: Background: The content of grandiose delusions—inaccurate beliefs that one has special powers, wealth, mission, or identity—is likely to be highly meaningful. The meaning, for example providing a sense of purpose, could prove to be a key factor in the delusion taking hold. We aimed to empirically define and develop measures of the experience of meaning in grandiose delusions and the sources of this meaning, and to test whether severity of grandiosity in clinical and non-clinical populations is associated with level of meaning. Methods: We did a cross-sectional self-report questionnaire study in two cohorts: non-clinical participants aged 18 years and older, with UK or Irish nationality or residence; and patients with affective or non-affective psychosis diagnoses, aged 16 years and older, and accessing secondary care mental health services in 39 National Health Service providers in England and Wales. Participants with high grandiosity completed two large item pools: one assessing the experience of meaning in grandiose delusions (Grandiosity Meaning Measure [termed gram]) and one assessing the sources of meaning (Grandiosity Meaning Measure–Sources [termed grams]). The Grandiosity Meaning Measure and Grandiosity Meaning Measure–Sources were developed using exploratory factor analysis and confirmatory factor analysis. Structural equation modelling was used to test the associations of meaning with the severity of grandiosity. The primary outcome measure for grandiosity was the Specific Psychotic Experiences Questionnaire (grandiosity subscale) and associations were tested with the Grandiosity Meaning Measure and the Grandiosity Meaning Measure–Sources. Findings: From Aug 30, 2019, to Nov 21, 2020, 13 323 non-clinical participants were enrolled. 2821 (21%) were men and 10 134 (76%) were women, 11 974 (90%) were White, and the mean age was 39·5 years (SD 18·6 [range 18–93]). From March 22, 2021, to March 3, 2022, 798 patients with psychosis were enrolled. 475 (60%) were men and 313 (39%) were women, 614 (77%) were White, and the mean age was 43·4 years (SD 13·8 [range 16–81]). The experience of meaning in relation to grandiose delusions had three components: coherence, purpose, and significance. The sources of meaning had seven components: positive social perceptions, spirituality, overcoming adversity, confidence in self among others, greater good, supporting loved ones, and happiness. The measurement of meaning was invariant across clinical and non-clinical populations. In the clinical population, each person typically endorsed multiple meanings and sources of meaning for the grandiose delusion. Meaning in grandiose delusions was strongly associated with severity of grandiosity, explaining 53·5% of variance, and with grandiose delusion conviction explaining 27·4% of variance. Grandiosity was especially associated with sense of purpose, and grandiose delusion conviction with coherence. Similar findings were found for the non-clinical population. Interpretation: Meaning is inherently tied to grandiose delusions. This study provides a framework for research and clinical practice to understand the different types of meaning of grandiosity. The framework is likely to have clinical use in psychological therapy to help guide patients to find sources of equivalent meaning from other areas of their lives and thereby reduce the extent to which the grandiose delusion is needed. Funding: Health Education England and National Institute for Health and Care Research.